Burden of Disease Attributed to Prenatal Methylmercury Exposure in the Yanomami Indigenous Land - Ana Claudia Santiago de Vasconcellos; Raiane Fontes de Oliveira; Marcos Wesley Oliveira; Paulo Cesar Basta (Toxics)
The Yanomami Indigenous Land (YIL) is heavily impacted by illegal gold mining, leading to significant contamination by methylmercury, a neurotoxin that poses severe risks to human health. The fetal brain is particularly susceptible to the neurotoxic effects of methylmercury, which can result in mild mental retardation (MMR). The goal of this study was to estimate the burden of disease (BoD) associated with methylmercury exposure in the YIL and its economic implications. The BoD calculations followed World Health Organization (WHO) methodologies. To estimate the local BoD, hair samples were collected from women of childbearing age in the Waikás, Mucajaí, Paapiu, and Maturacá regions. For broader estimates, data from the scientific literature were used. The average hair methylmercury concentrations in these investigated regions were 6.21 µg/g, 3.86 µg/g, 3.53 µg/g, and 2.96 µg/g, respectively. The MMR incidence rate (IR) in children ranged from 2.08 to 4.47 per 1000 in these regions. The Disability-Adjusted Life Years (DALYs) per 1000 births varied from 24.8 to 53.4. In the Worst-Case Scenario, MMR-IR reached 9 per 1000, with DALYs per 1000 births rising to 109.6. The estimated economic impact of methylmercury exposure ranged from USD 716,750 to USD 3,153,700. This study is the first to quantify the MMR incidence due to mercury in the YIL, highlighting the severe threat posed by gold mining to the health and survival of the Yanomami people.